Implementation of Cloud Computing and the Competitiveness of Small and Micro Trading Companies in the Province of Huancayo - Cabrera Córdova, Ciro Nicolai (2023)
Currently, Small and Micro Companies are the main source of employment in Peru with 80% of the labor supply according to the Ministry of Labor. In this new post-pandemic environment, it is crucial for the subsistence of this type of company to start the process of digital transformation and improve its competitiveness. The purpose of this paper is to determine the influence of the implementation of Cloud Computing on the competitiveness of MYPES in the province of Huancayo, for which a non-experimental-quantitative, descriptive and cross-sectional investigation was designed and executed. The collection instrument was the questionnaire composed of 70 questions in total, of which 19 were to know the main characteristics of MYPES, 15 related to the level of adoption of Cloud Computing in MYPES (IAAS, PAAS and SAAS) and 36 focused To evaluate competitiveness through its factors (Quality Assurance, Commercialization or Marketing, Accounting and Finance, Human Resources, and Technology) these indicators were measured using the Likert scale. This questionnaire was applied to 322 trading companies in the Province of Huancayo; As a result, the level of adoption of Cloud Computing in each of these companies and its influence (correlation) on the main factors of their competitiveness are indicated. These results allow drawing conclusions about the level of relationship between Business Competitiveness and the Adoption of Cloud Computing, which could be extrapolated to other regions of Peru.